Answers:
y = -25
y = 7
Step-by-step explanation:
Find the derivative of the function.
[tex]\frac{dy}{dx} y = 3x^2-6x-9[/tex]
The zeros of the derivative are the local extrema (Maximum & Minimum)
[tex]0 = 3x^2-6x-9[/tex]
Take out the greatest common factor, 3, to get this equation:
[tex]0 = 3(x^2-2x-3)[/tex]
Factor out the brackets.
[tex]0 = 3(x - 3) ( x + 1 )[/tex]
You are left with two possible values for x:
x = 3
x = -1
By substituting each value into the original function [tex]y = x^3 - 3x^2 - 9x + 2[/tex], you get the equation of any horizontal tangents to the curve.
When x = 3:
[tex]y = (3)^3 - 3(3)^2 - 9(3) + 2 = -25[/tex] Meaning y = -25
When x = -1:
[tex]y = (-1)^3 - 3(-1)^2 - 9(-1) + 2 = 7[/tex] Meaning y = 7